Building peace one school at a time: a case study for Catholic schools in South Africa. Issue 2 (3rd July 2021) - Baker, Anne; MacKenzie, Cullen; McCormick, John
Abstract : South African democracy was born in 1994 after years of oppression and dehumanisation. Through the implementation of Child Safeguarding Policies from 2012, deep unhappiness in schools was uncovered and the use of corporal punishment which was abolished in 1996 became apparent. Teachers were adamant that corporal punishment was the only means of discipline that worked and most school discipline processes were punitive, leading to a breakdown in relationships. Faced with this challenge, the Catholic Institute of Education developed a programme based on Restorative Justice to strengthen relationships and manage conflict and tensions. The Building Peaceful Schools programme began in 2013 using an iterative process which involved three workshops: Peacebuilding, Conflict Management and Restorative Justice. In order to measure change impacts, a school climate survey for pupils was added in 2016. Results suggest slow but steady improvement.